Strategi Pengelolaan Keuangan Berdasarkan Prinsip Matematika Sederhana - Ridayati, Ridayati; Puji Astutik, Herna (ReTII, 2024)
The financial management training program based on simple mathematical principles was conducted in Padukuhan Dobalan, Kapanewon Timbulharjo, Bantul Regency. This initiative aimed to improve the financial literacy of the rural community, especially in preparing for potential economic recession. Most of the residents work as farmers and laborers, making them vulnerable to global economic changes. The program introduced the use of basic mathematical operations addition, subtraction, multiplication, and division to create budgets, track expenses, and make sound financial decisions.The training employed pretests and posttests to measure participants' progress. The results showed a significant improvement in the participants' ability to manage their finances and adopt positive mindsets, as indicated by higher posttest scores compared to pretest scores. The program also encouraged participants to reduce unnecessary expenses, seek additional income sources, invest for future growth, and share their wealth through charity.Overall, the program had a positive impact on the participants’ financial management skills and household economic resilience. However, some participants may still require further guidance to achieve maximum results. This initiative is expected to continue and serve as a model for empowering communities to face economic challenges more wisely and strategically.